Redefining the Influence of Ethnicity on Simultaneous Kidney and Pancreas Transplantation Outcomes: A 15-year Single-center Experience. Issue 1 (January 2020) - Young, Carlton J.; MacLennan, Paul A.; Mannon, Elinor C.; Reed, Rhiannon D.; Shelton, Brittany A.; Hanaway, Michael J.; Agarwal, Gaurav; Gaston, Robert S.; Julian, Bruce A.; Kew, Clifton E.; Kumar, Vineeta; Mannon, Roslyn B.; et al.
Abstract : Objective: To examine the largest single-center experience of simultaneous kidney/pancreas transplantation (SPK) transplantation among African-Americans (AAs). Background: Current dogma suggests that AAs have worse survival following SPK than white recipients. We hypothesize that this national trend may not be ubiquitous. Methods: From August 30, 1999, through October 1, 2014, 188 SPK transplants were performed at the University of Alabama at Birmingham (UAB) and 5523 were performed at other US centers. Using Kaplan-Meier survival estimates and Cox proportional hazards regression, we examined the influence of recipient ethnicity on survival. Results: AAs comprised 36.2% of the UAB cohort compared with only 19.1% nationally ( P < 0.01); yet, overall, 3-year graft survival was statistically higher among UAB than US cohort (kidney: 91.5% vs 87.9%, P = 0.11; pancreas: 87.4% vs 81.3%; P = 0.04, respectively) and persisted on adjusted analyses [kidney adjusted hazard ratio (aHR): 0.58, 95% confidence interval (95% CI) 0.35–0.97, P = 0.04; pancreas aHR: 0.54, 95% CI 0.34–0.85, P = 0.01]. Among the UAB cohort, graft survival did not differ between AA and white recipients; in contrast, the US cohort experienced significantly lower graft survival rates among AA than white recipients (kidney 5 years: 76.5% vs 82.3%, P < 0.01; pancreas 5 years: 72.2% vs 76.3%, P = 0.01; respectively). Conclusion: Among a single-center cohort of SPK transplants overrepresented by AAs, we demonstrated similar outcomes among AA and white recipients and better outcomes than the US experience. These data suggest that current dogma may be incorrect. Identifying best practices for SPK transplantation is imperative to mitigate racial disparities in outcomes observed at the national level. Abstract : Supplemental Digital Content is available in the text